Towards a Practical and Empirically Grounded Account of Útang-na-Loób as a Filipino Virtue - Cleofas, Jacklyn A. (Archīum Ateneo, 2024)
Although there are existing philosophical accounts of útang-na-loób (debt of good will) and the suggestion that this Filipino cultural practice can be considered a virtue is not new, questions remain about how morally desirable forms of útang-na-loób can be separated from its problematic involvement in nepotism, patronage politics, life-long servitude, corruption, and other forms of injustice. In this paper, I develop a practical and empirically grounded account of útang-na-loób as a Filipino virtue by using a neo-Aristotelian framework that allows for the incorporation of research from the social sciences into virtue-theoretic recommendations for action. I argue that útang-na-loób must be understood in conjunction with a distinctly Filipino understanding of justice (katarúngan), especially on what counts as fair distribution of resources and opportunities, to promote culturally rooted social harmony (pagkakáisá) and communal flourishing. The paper ends with a brief discussion of a case to demonstrate how útang-na-loób can be lived out in a morally desirable way.